2019
DOI: 10.21608/zjar.2019.33385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date and Foliar Spray With Potassium Silicate on Growth and Yield of Some Garlic Cultivars

Abstract: A field experiment was carried out during the two successive winter seasons of 2016/2017 and 2017/2018 in a private Farm at Hehia Distrect, Sharkia Governorate, Egypt, to study the effect of planting date, and foliar spray with potassium silicate on dry weight, bulb yield and its components of Balady and Sids 40 garlic cultivars under clay soil conditions and using flood irrigation system. The obtained results indicated that planting Balady cultivar on 1 st Oct. and spraying with potassium silicate (K silicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The use of natural potassium fertilizer (Feldspar) or bio-fertilizer (Potassium solubilizing bacteria) is low cost resources which could alternate the expensive applied K-chemical fertilizers. ( Mohamed et al 2019) indicated that spraying garlic with potassium silicate increased dry weight of leaves/plant, bulb and total dry weight/plant, yields of, exportable, marketable and total yield/fed., as well as average bulb weight.…”
Section: Introductionmentioning
confidence: 98%
“…The use of natural potassium fertilizer (Feldspar) or bio-fertilizer (Potassium solubilizing bacteria) is low cost resources which could alternate the expensive applied K-chemical fertilizers. ( Mohamed et al 2019) indicated that spraying garlic with potassium silicate increased dry weight of leaves/plant, bulb and total dry weight/plant, yields of, exportable, marketable and total yield/fed., as well as average bulb weight.…”
Section: Introductionmentioning
confidence: 98%